Corporate Social Responsibility: A Constitutional Perspective - Ali Safa’at, Muchamad (Mahkamah Konstitusi Republik Indonesia, 2014)
Originally, the concept of CSR was come from business ethic values that impose corporation’s ethical responsibly to their social and natural environment. That development of ethical business was part of social consciousness on the degradation of environment as impact of corporation activities. This reality also raised the deep environmental ethic or deep ecology which challenge anthropocentrism economical development and urged ecocentrism development. In Indonesia, this phenomenon was marked by the enactment of Act 4/1982 on Environmental Management.The constitutional debate on CSR just began when the Indonesian Constitutional Court heard and decided the judicial review case of Act 40/2007 on Limited Liability Company which stipulate CSR mandatory law for corporation that have activity in natural resources areas. In its decision, Constitutional Court refused the petition. This means that the court affirmed that CSR mandatory law is not contrary to the Constitution. However, the legal argumentation of the court was not shifted from economical and environmental perspectives. The constitutional basis of the decision is Article 33 (4) concerning national economic principles and Article 33 (3) concerning state power on land, water, and natural resources. The Constitutional Court did not use the human rights concept as the source of CSR mandatory law.In constitutional law perspective, we can justify the CSR mandatory law from human rights guarantee on the constitution. CSR is one of the obligations to respect, to protect, to fulfill, and to promote human rights. Those obligations are not only bind over the government, but also corporation and all citizens. In that perspective, CSR should be mandatory law not only for the corporation which manage or correlate with natural resource, but for all corporations that operate in the middle of the society.